Dynamic Relationship between Agriculture and Carbon Emissions in Indonesia: Evidence From Stirpat Model - Nur, T. M.; Elfiana, Elfiana; Desparita, Naya; Muttaqim, Hakim; Fachrurrozi, Kamal (International Journal of Energy Economics and Policy, 2025)
Over the past few decades, Indonesia's agricultural sector has become the backbone of the economy. However, the agricultural sector faces environmental challenges. Most agricultural activities are related to carbon emissions. This study aims to analyze the relationship between Indonesia's agricultural sector, renewable energy, and carbon emissions using STIRPAT model. The research data covers from 1990 to 2021. The analysis models used are ARDL, FMOLS, DOLS, and causality. The results of the study found that economic growth and population have a positive and significant effect in the long term. The findings show a negative and significant impact on the agricultural and renewable energy sectors. In the short-term estimate, only the agricultural sector, renewable energy, and population have a significant effect. The results of FMOLS and DOLS found that the long-term estimate is valid and reliable. In addition, some findings support the causality of the agricultural sector with renewable energy, which can affect economic growth and the relationship between population and carbon emissions. This study is expected to help policymakers mitigate carbon emissions.